Bridging the divide: barriers and facilitators to equitable community-academic partnerships in health research - Khatib, Maissa; Shah, Rushabh; Mendhe, Surbhi; Whisner, Corrie; Buman, Matthew (Frontiers in Public Health, 2025)
ObjectiveThis study explores best practices for fostering sustainable and equitable community-academic partnerships in public health, focusing on identifying key barriers, facilitators, and health priorities among historically underrepresented populations in Arizona—including Latinx, Native American, African American, LGBTQ+, immigrant, and refugee communities. Grounded in the Community-Based Participatory Research (CBPR) model, the study emphasizes equity, shared power, and collaborative engagement.MethodUsing a descriptive qualitative approach, the study draws on 21 in-depth interviews—combining semi-structured and vignette-based formats—with academic researchers, community members, and community partners. Thematic analysis was conducted across three CBPR-aligned domains: (1) challenges to equitable partnerships, (2) practices that foster collaboration, and (3) community-identified health priorities.ResultsFindings revealed seven key themes across the three domains. Under Domain 1 (Challenges to Equitable Partnerships), participants identified three primary barriers: (1) misaligned funding structures and short-term grants, (2) institutional bureaucracy and academic incentive systems that deprioritize community engagement, and (3) mismatched timelines and priorities between academic researchers and community partners. Domain 2 (Practices that Foster Collaboration) highlighted three themes that support effective partnerships: (4) trust-building through cultural humility and transparency, (5) shared decision-making and mutual empowerment, and (6) commitment to sustained engagement beyond project timelines. Finally, Domain 3 (Community-Identified Health Priorities) surfaced a seventh theme: (7) mental health stigma, lack of culturally responsive care, and structural barriers such as poverty, immigration status, and geographic isolation.ConclusionThis study contributes to the literature on equitable community-academic partnerships by offering actionable strategies grounded in lived experience. Emphasizing continuous engagement, co-leadership, and alignment with community-defined priorities, these findings support the development of culturally relevant, context-specific interventions that address health disparities in historically marginalized populations. The lessons from Arizona are transferable to other underserved regions, reinforcing the need for structural reforms and relationship-centered research practices.